(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Track and field athletics has traditionally been one of the fundamental and most widespread sports disciplines, playing a significant role in the physical development of young people and in the formation of a broader sports culture. However, contemporary social and informational transformations, along with the declining level of physical activity among the younger generation, have led to a gradual decrease in interest in this sport. The issue becomes especially relevant under the conditions of martial law in Ukraine, when psychological, social, and infrastructural factors substantially influence the sporting preferences of university students and shape their daily behavioural patterns. The study presents the results of a survey conducted among higher education students regarding their level of interest in track and field athletics, the frequency with which they follow competitions, the perceived impact of martial law, and the factors shaping their motivational orientations. Particular attention is paid to the analysis of online search dynamics based on Google Trends data for the years 2021–2025, which makes it possible to assess broader digital patterns related to the popularity of track and field athletics in Ukraine and worldwide, as well as to identify emerging fluctuations in public attention. The findings indicate that, despite an overall decline in interest among part of the youth population, there remains a group of students with stable or even increasing motivation, highlighting the potential of this sport as a means of psychological support, stress reduction, and personal development under crisis conditions. The study provides an analytical foundation for further scientific research and for the development of strategies aimed at promoting track and field athletics during martial law as well as throughout the post-war recovery period, when rebuilding physical culture and restoring community well-being will be of particular importance.